The embodiment of Qian Zhongshu's Guan Zhui Bian in an internet novel: Xuanxue and metaphor - Wang, Aiqing (LingTera, 2024)
As an iconic intellectual, novelist, translator and poet in the 20th century, é’±é’Ÿä¹¦ Qian Zhongshu (1910-1998) was not only celebrated for literary aptitude, epitomised by his chef-d'oeuvre å›´åŸŽ Wei Cheng "˜Fortress Besieged' (serialised 1946-1947), but also for his unrivalled erudition, multilingualism and critical acumen. Qian Zhongshu was versed in Chinese and Western studies, encompassing literature, philosophy, psychology, history, aesthetics, etc. Qian Zhongshu's commendable scholarly research can be exemplified by an encyclopaedic masterpiece entitled ç®¡é”¥ç¼– Guan Zhui Bian "˜Limited Views: Essays on Ideas and Letters' (1979), which is constituted of a prodigious amount of reading notes and essays written in concise, recondite Classical Chinese. Notwithstanding its self-deprecating title, Guan Zhui Bian has attained critical plaudits. In a web-based time-travel novel ä¸Šå“å¯’å£« Shangpin Han Shi "˜A Top-Ranked Impoverished Scholar' (2009-2011) composed by a writer pseudonymised as è´¼é“ä¸‰ç—´ Zeidaosanchi, the author deployed elements from Guan Zhui Bian, which defies the stereotype that male-authored and male-oriented online narratives are prone to be "˜feel-good writing' marked by æ„æ·« yi yin "˜lust of the mind; mental pornography'. To be more specific, the author drew on Qian Zhongshu's elaboration of çŽ„å¦ xuanxue (Lit. "˜learning in the profound') and analyses of metaphor.